VALIDITY OF OSTEOPOROSIS SELF-ASSESSMENT TOOL FOR ASIANS (OSTA) FOR MASS SCREENING AMONG DIVERSE POPULATION OF MALAYSIA - Myint Swe; Biju Benjamin; John Anantham; Esther Gunaseli; Sin Fah Chung (Asian Journal of Medicine & Health Sciences, 2019)
Introduction: Osteoporosis Self-assessment Tool for Asian (OSTA) has been recommended as a valid tool for screening osteoporosis in many countries. In Malaysia, effectiveness of OSTA has been validated only for Malay women. However, there is no such data for heterogeneous Malaysian population including Chinese, Malay and Indians. Methods: One hundred postmenopausal women from Kinta district, Ipoh, Malaysia were randomly selected. After measuring the body weight, OSTA scoring was calculated. Bone mineral density (BMD) was measured on the same day. Results: The sensitivity and specificity of OSTA for all participant groups by comparing with BMD results were 52.6% and 67.7% for spine and 46.7% and 65.5% for hip. This was in agreement with most of the other studies from Asian region. Conclusion: By our findings it is not conclusive to recommend the OSTA for screening purpose like other studies. It is advisable that a larger study should be done in the future involving many participants, in collaboration with government hospital to reduce the cost for BMD measurement.